โครงการสินเชื่อเพื่อปลูกสร้างบ้านภายใต้ความร่วมมือระหว่าง ธนาคารอาคารสงเคราะห์กับสมาคมธุรกิจรับสร้างบ้าน - ณรงค์ หาเรือนเงิน (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
To follow up the operation of housing loan projects for home construction in collaboration with the Government Housing Bank and the Home Builder’s Association and to suggest better ways for the bank to achieve its goals. The research was conducted by reviewing the bank’s documents, interviewing 359 subjects who did not participate in this project and 28 subjects who did participate in this project by telephoning them and mailing them a questionnaire. Both groups of subjects applied for a housing construction loan and mortgaged their collateral in Bangkok, Nontaburi, Patumtani and Samut Prakarn from January 2005 to December 2006. Nine house construction companies which built houses for the bank’s customers during the same period and four related administrators from four sections of the bank which are in charge of the project were also interviewed. The results are as follows: 1) The process of approving loans for this project was different from that of existing housing loans in terms of 1.1. the appraisal of the building and the building itself being used as collateral and 1.2. the number of installments to be paid and the interest rate during construction. 2) The number of borrowers participating in this project was smaller than expected because 2.1. 88.6% of the borrowers were not informed about this project and if they had been informed earlier, 89.7% of them would have applied for this loan. 2.2 The bank and the housing construction companies which are members of the Home Builder’s Association did not cooperate well. The companies did not promote this project to their customers. And 2.3. the procedure of applying for housing loans was more complicated than that of other commercial banks. As a result, the housing construction companies did not recommend this project to their customers. Suggestions for improving this project are as follows: 1. The bank should ask those housing construction companies to continually and actively inform the public about this project through available advertising channels. 2. The bank should set up a special unit to work jointly with the housing construction companies to facilitate the procedure of applying for housing loans. And 3. the loan target of 2,500 million baht a year is too high so the bank should survey the market first to find the appropriate level.